Evaluasi Kecepatan Gelombang Geser Tanah Berbasis Data Mikrotremor di Kawasan Karst Rammang-Rammang Maros TN Babul - Hasaniyah, Sitti; Arsyad, Muhammad; Susanto, Agus (Jurusan Fisika FMIPA Universitas Andalas, 2025)
This study aims to identify the profile of shear wave velocity (Vs30) and to analyze the classification of soil types of the Rammang-Rammang Maros Karst Area based on Vs30 value. This research was carried out at Rammang-Rammang Maros Karst Area, Salenrang and Bontolempangan Village, Bontoa District, Maros Regency, South Sulawesi. The method used in this research was the Horizontal to Vertical Spectral Ratio (HVSR) method to produce the HVSR curve and then analysed in the inversion method using Dinver to produce a ground profile. The Vs30 values were obtained in the range from 249 to 1384 m/s. The characteristics of the rock response could indicate the specifications of a rock type. Based on the Vs30 values, it was found that the classification of rock (SB) located around the karst hilly areas, soft rock (SC) located around the residential areas and the river, and stiff soil (SD) located near ricefield. The overall seismic risk in the research area is low based on Vs30 values below 200 m/s. These findings provide essential baseline data to support sustainable land use and tourism development planning in the region.